2019
DOI: 10.1080/10758216.2019.1640068
|View full text |Cite
|
Sign up to set email alerts
|

Proletarian Internationalism in Action? Communist Legacies and Attitudes Towards Migrants in Russia

Abstract: The goal of the paper is to investigate the effect of the Communist legacies on the attitude towards migrants in the present-day Russia. Since mid-first decade of the 2000s, Russia established itself as an attractive center of labor migration, with hundreds of thousands of migrant workers from Central Asia, Southern Caucasus and Moldova entering the Russian labor market. This rise of migration triggered an upsurge in the xenophobic sentiment and nationalism. This paper, looking at the variation of anti-migrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 96 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…Polish xenophobia has its roots in centuries-old antisemitism (Bilewicz et al 2012) and the legacy of the communist regime. Not only did communism render Poland a nationally and ethnically homogeneous state, but it also combined it with a homogenic and nationalist ideology, which strengthened the society's suspicion of others, including foreigners, and even made some groups national enemies (Libman and Obydenkova 2020;Burjanek 2001;Zarycki 2008). All this is combined with the process of Poles abandoning European values, set in motion in 2015, known as de-Europeanisation, which includes departure from tolerance (Vermeersch 2019).…”
Section: Two-folding '3d'-unwanted and 'Essentially' Wanted Immigrants Vis-à-vis Governmental Xenophobiamentioning
confidence: 99%
“…Polish xenophobia has its roots in centuries-old antisemitism (Bilewicz et al 2012) and the legacy of the communist regime. Not only did communism render Poland a nationally and ethnically homogeneous state, but it also combined it with a homogenic and nationalist ideology, which strengthened the society's suspicion of others, including foreigners, and even made some groups national enemies (Libman and Obydenkova 2020;Burjanek 2001;Zarycki 2008). All this is combined with the process of Poles abandoning European values, set in motion in 2015, known as de-Europeanisation, which includes departure from tolerance (Vermeersch 2019).…”
Section: Two-folding '3d'-unwanted and 'Essentially' Wanted Immigrants Vis-à-vis Governmental Xenophobiamentioning
confidence: 99%
“…Finally, a set of studies connects the nature, development, and effects of Eurasian regional governance to a number of profound historical issues that make the Eurasian regionalism critically different from regional governance elsewhere in the world. The literature on historical legacies in general and on post-Communist legacies in particular, has been growing in the last decades to explain democratic development, attitudes, behavioural patterns (e.g., corruption), economic development (e.g., inequality, firm innovation, development of bank sector, foreign direct investment), the mass media, political discourse and even entertainment in Central European States and in the former Soviet republics (Beissinger, 2002;Beissinger & Kotkin, 2014;Lankina et al, 2016a;Libman & Obydenkova, 2019a, 2019bObydenkova & Libman, 2015;Pop-Eleches, 2007;Pop-Eleches & Tucker, 2013). Among other issues, these studies have also indicated at the persistence and survival of profound economic and social links, especially the channels of foreign trade created during the USSR and the importance of migration and lingua franca that survives due to the mass media in Russia as well as the use of cyber-space as an entertainment.…”
Section: Differences Across Eurasian Regional Organisationsmentioning
confidence: 99%
“…On the other hand, a different set of studies looked into historical roots of success and failure in democratic development of post-Communist regions. This includes a vast literature focusing on corruption, intolerance to migrants, the democratic and governance deficits in post-Soviet Eurasia and on the role of various historical legacies explaining these phenomena (Beissinger and Kotkin 2014;Dinino and Orttung 2005;Hellman 1998;Segbers 2001;Trochev 2008;Bunce and Wolchik 2011;Hough 2004;Fish 2005;Obydenkova and Swenden 2013;Wilson 2005;Hale 2005Hale , 2006Hale , 2015Libman and Obydenkova 2019;2014;Nazarov and Obydenkova 2020;Allina-Pisano 2007;Abdelal 2010;Pop-Eleches and Tucker 2017) in addition to studies looking into legacies of the Cold World War at the world-wide level (e.g., Ben-Artzi 2016; Obydenkova and Vieira 2020). In the universe of historical legacies, the paper focuses on the specific group of Communist, or, following Jowitt (1992), Leninist, legaciesthat is, the persistent social and political phenomena that are observed in post-Communist countries in spite of the disappearance of the original political and social environment of the Communist regimes.…”
Section: Introductionmentioning
confidence: 99%